The exploitation of host autophagy and ubiquitin machinery by Mycobacterium tuberculosis in shaping immune responses and host defense during infection. Issue 1 (2nd January 2023) - Shariq, Mohd; Quadir, Neha; Alam, Anwar; Zarin, Sheeba; Sheikh, Javaid A.; Sharma, Neha; Samal, Jasmine; Ahmad, Uzair; Kumari, Indu; Hasnain, Seyed E.; Ehtesham, Nasreen Z.
ABSTRACT: Intracellular pathogens have evolved various efficient molecular armaments to subvert innate defenses. Cellular ubiquitination, a normal physiological process to maintain homeostasis, is emerging one such exploited mechanism. Ubiquitin (Ub), a small protein modifier, is conjugated to diverse protein substrates to regulate many functions. Structurally diverse linkages of poly-Ub to target proteins allow enormous functional diversity with specificity being governed by evolutionarily conserved enzymes (E3-Ub ligases). The Ub-binding domain (UBD) and LC3-interacting region (LIR) are critical features of macroautophagy/autophagy receptors that recognize Ub-conjugated on protein substrates. Emerging evidence suggests that E3-Ub ligases unexpectedly protect against intracellular pathogens by tagging poly-Ub on their surfaces and targeting them to phagophores. Two E3-Ub ligases, PRKN and SMURF1, provide immunity against Mycobacterium tuberculosis ( M. tb ). Both enzymes conjugate K63 and K48-linked poly-Ub to M. tb for successful delivery to phagophores. Intriguingly, M. tb exploits virulence factors to effectively dampen host-directed autophagy utilizing diverse mechanisms. Autophagy receptors contain LIR-motifs that interact with conserved Atg8-family proteins to modulate phagophore biogenesis and fusion to the lysosome. Intracellular pathogens have evolved a vast repertoire of virulence effectors to subdue host-immunity via hijacking the host ubiquitination process. This review highlights the xenophagy-mediated clearance of M. tb involving host E3-Ub ligases and counter-strategy of autophagy inhibition by M. tb using virulence factors. The role of Ub-binding receptors and their mode of autophagy regulation is also explained. We also discuss the co-opting and utilization of the host Ub system by M. tb for its survival and virulence. Abbreviations: APC: anaphase promoting complex/cyclosome; ATG5: autophagy related 5; BCG: bacille Calmette-Guerin; C2: Ca 2+ -binding motif; CALCOCO2: calcium binding and coiled-coil domain 2; CUE: coupling of ubiquitin conjugation to ER degradation domains; DUB: deubiquitinating enzyme; GABARAP: GABA type A receptor-associated protein; HECT: homologous to the E6-AP carboxyl terminus; IBR: in-between-ring fingers; IFN: interferon; IL1B: interleukin 1 beta; KEAP1: kelch like ECH associated protein 1; LAMP1: lysosomal associated membrane protein 1; LGALS: galectin; LIR: LC3-interacting region; MAPK11/p38: mitogen-activated protein kinase 11; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MAP3K7/TAK1: mitogen-activated protein kinase kinase kinase 7; MAPK8/JNK: mitogen-activated protein kinase 8; MHC-II: major histocompatibility complex-II; MTOR: mechanistic target of rapamycin kinase; NBR1: NBR1 autophagy cargo receptor; NFKB1/p50: nuclear factor kappa B subunit 1; OPTN: optineurin; PB1: phox and bem 1; PE/PPE: proline-glutamic acid/proline-proline-glutamic acid; PknG: serine/threonine-protein kinase PknG; PRKN: parkin RBR E3 ubiquitin protein ligase; RBR: RING-in between RING; RING: really interesting new gene; RNF166: RING finger protein 166; ROS: reactive oxygen species; SMURF1: SMAD specific E3 ubiquitin protein ligase 1; SQSTM1: sequestosome 1; STING1: stimulator of interferon response cGAMP interactor 1; TAX1BP1: Tax1 binding protein 1; TBK1: TANK binding kinase 1; TNF: tumor necrosis factor; TRAF6: TNF receptor associated factor 6; Ub: ubiquitin; UBA: ubiquitin-associated; UBAN: ubiquitin-binding domain in ABIN proteins and NEMO; UBD: ubiquitin-binding domain; UBL: ubiquitin-like; ULK1: unc-51 like autophagy activating kinase 1.